Política urbana perante a efetividade dos direitos fundamentais - Tezine, Adriana Vacare (2011)
The aim of the current work is to search on a survey and to highlight what are the legal procedures which generates the effectiveness on the fundamental laws being performed in urban police, being it from the new definition brought by the Federal Constitution and under Law n. 10.257/01 City Statute. Such study may be justified due to the need on turning it onto real and effective the fundamental rights intrinsic to the Human being itself and, aiming in having it granted formally in legal texts. The urban issue is global due to dealing with local issues where people usually, the majority, live. The accomplishment of basic rights is a subject that has been caught into attention from the jurisconsult, whether being from the State, Society and specially by the ripening of the Democratic State (Brazilian Rights). Article 182 from Carta Magna adjudicates the public power, municipal one, the competence to perform the urban police on development, aimed in organizing the entire growth of social functions on the city and assuring the wellness of its population as of the general guidelines settled under the law. The urban politics, a legal and belonging to the State law, is required in order to control the urban growth, highlighted upon new rules settled by the City Statute, which imposed relevant guidelines as the sustainable cities´ right to it, understood as the right to urban housing, environment sanitation, urban infrastructure, transportations and public services, besides work, leisure, for the current one and future generations; democratic management by the taking part of the population and associations representing distinct segments of a community; the need of planning and to cooperate among federated, society and so far. In order to have such work developed the object of this study has been urban politics, its guidelines and the instruments containing into the City Statute; Municipal organ, competencies of federated beings on urban tasks; the set of rules besides the principles compounding the Urban Law; fundamental rights, its systematic and specific application on urban politics. Thus, it is presented three mechanisms which contribute for the effectiveness of fundamental law on urban politics, undertaken in the Federal Constitution and the City Statute: finally, the assurance of having the participative democracy; the broaden chance to access to judiciary basis, highlighting the institution of urban side of it, such as the forensic tutorship coming from the public civil action besides the systemic and global protection of human rights